Die Trajektlinie Spyck-Welle erweiterte ab 1865 den internationalen Zugverkehr zwischen dem Deutschen Reich und den Niederlanden. Den Rhein ohne Brücke „überbrücken“ - Korte, Peter (Kalender für das Klever Land, 2025)
Keywords: Deutschland; Eisenbahnfähre; Eisenbahnlinie; Eisenbahnnetz; Emmerich am Rhein; Fähre; Grenzgebiet; Kleve (Kreis Kleve); Rhein; Zevenaar

Spannung und Widerstand an der niederländischen Grenze 1930–1940. Exil, Widerstand und niederländische Unterstützung. Zwei Beispiele in der Region Kleve-Nijmegen - Brauer, Jan (Dies- und jenseits der Grenze. Translokale Prozesse und ihre Einwirkung auf den deutsch-niederländischen Grenzraum, 2017)
Keywords: Deutscher Flüchtling; Exil; Grenzgebiet; Kleve (Kreis Kleve); Nimwegen; Widerstand

Aan de Hollands-Duitse stamtafel. Het Consulaat der Nederlanden in Kleef in roerige tijden 1920–1960 - Brauer, Jan (Gelderland grensland. 2000 jaar verdeeld en verbonden, 2016)
Keywords: Grenzgebiet; Kleve (Kreis Kleve); Konsulat

Grenskloosters en de naderende Klostersturm. Religieuzen en de eerste confrontaties met de nazi-staat langs de Nederlandse grens tussen 1930 en 1940 - Brauer, Jan (Dienstbaar onder vuur. Religieuzen en de Tweede Wereldoorlog, 2016)
Keywords: Grenzgebiet; Kloster; Orden

Socio-cultural proximity, daily life and shopping tourism in the Dutch–German border region - Szytniewski, Bianca; Spierings, Bas; Velde, Martin van der (Tourism Geographies, 2016)
Abstract: „This paper analyses feelings of socio-cultural proximity and distance with a specific focus on the tourist experience in cross-border shopping and everyday life practices in border regions. We examined shopping practices of Dutch border crossers who visit the German town Kleve in the Dutch–German border region. This particular border context has allowed us not only to reflect on a multidimensional approach towards socio-cultural proximity and distance, but also to examine how these different dimensions express themselves in the tourist experience when it comes to people and places that are geographically ‘close’ but assumingly socially and culturally ‘distant’ from home. Although some differences prompted feelings of discomfort, in particular, differences in social engagement, feelings of comfort stand out in our analysis of cross-border shopping tourism. Furthermore, our study shows that shopping tourism and exoticism, on the one hand, and everyday routines and the mundane, on the other hand, are closely intertwined in the lives of people living in a border region, resulting in a fluid interpretation of the exotic and the mundane in the cross-border context.“
Keywords: Einkaufen; Grenzgebiet; Kleve (Kreis Kleve); Mobilität; Sozialraum; Tourismus; Verbrauch

Schmuggeln - einst für Grenzanrainer oft überlebenswichtig - Rühl, Hans (Kalender für das Klever Land, 2006)
Keywords: Grenzgebiet; Kleve (Kreis Kleve); Schmuggel

Die Trajektlinie Zevenaar - Elten - Welle - Spyck - Griethausen - Kleve - Roos, Dieter (Bundesbahn-Fahrbeamtenverein, 1983)
Keywords: Deutschland; Eisenbahnfähre; Eisenbahnlinie; Eisenbahnnetz; Emmerich am Rhein; Fähre; Grenzgebiet; Kleve (Kreis Kleve); Rhein; Zevenaar